2012
DOI: 10.1016/j.mad.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction increases skeletal muscle mitochondrial respiration but not mitochondrial content in C57BL/6 mice

Abstract: Dietary restriction (DR) is suggested to induce mitochondrial biogenesis, although recently this has been challenged. Here we determined the impact of 1, 9 and 18 months of 30% DR in male C57BL/6 mice on key mitochondrial factors and on mitochondrial function in skeletal muscle, relative to age-matched ad libitum (AL) controls. We examined proteins and mRNAs associated with mitochondrial biogenesis and measured mitochondrial respiration in permeabilised myofibres using high resolution respirometry. 30% DR, irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 65 publications
7
29
0
Order By: Relevance
“…Mitochondrial dysfunction likely contributed to this metabolic shift. Consistent with previous reports that mitochondrial function declines with aging (16,21,25), we found that the OCR in muscles of older rats was only 60% of that in young rats under basal conditions. Compared with OXPHOS, glycolysis is a less efficient way to generate ATP; thus, aging muscles may experience ATP deficiency when they have impaired mitochondrial function and depend more on glycolysis as the energy source.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Mitochondrial dysfunction likely contributed to this metabolic shift. Consistent with previous reports that mitochondrial function declines with aging (16,21,25), we found that the OCR in muscles of older rats was only 60% of that in young rats under basal conditions. Compared with OXPHOS, glycolysis is a less efficient way to generate ATP; thus, aging muscles may experience ATP deficiency when they have impaired mitochondrial function and depend more on glycolysis as the energy source.…”
Section: Discussionsupporting
confidence: 92%
“…The simultaneous determination of OXPHOS and glycolysis enables the elucidation of the shift between these two pathways with aging and after interventions. Using this new technology, we tested the first hypothesis of this study, that the CR-induced positive effects on muscle mass are associated with an improvement in cellular metabolism.To date, most studies have focused on examining the effects of "life-long" CR, where CR was initiated when animals were still growing and the effects were evaluated when the animals were at an advanced age (16,25,34). Recently, it has been suggested that the effects of CR are age dependent.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are inconsistent with a previous report that CR enhanced mitochondrial biogenesis in various tissues, including WAT and liver (Nisoli et al ., 2005). In contrast to that, however, certain reports suggested that CR did not induce mitochondrial biogenesis or increase mitochondrial content (Hempenstall et al ., 2012; Lanza et al ., 2012). Although the reasons for these discrepancies are unclear, they might result from differences in experimental conditions, including onset age or duration of CR, strain backgrounds of mice, diet components, and housing environments.…”
Section: Discussionmentioning
confidence: 99%